Nuclear-Encoded Plastidal Carbonic Anhydrase Is Involved in Replication of Bamboo mosaic virus RNA in Nicotiana benthamiana - Chen, I.-Hsuan; Tsai, April Y.; Huang, Ying-Ping; Wu, I.-Fan; Cheng, Shun-Fang; Hsu, Yau-Heiu; Tsai, Ching-Hsiu (Frontiers in Microbiology, 2017)
On inoculation of Nicotiana benthamiana with Bamboo mosaic virus (BaMV), a gene with downregulated expression was found involved in the infection cycle of BaMV. To uncover how this downregulated gene affects the accumulation of BaMV in plants, we used loss- and gain-of-function experiments. Knockdown of this gene decreased the accumulation of BaMV coat protein to approximately 60% in both plants and protoplasts of N. benthamiana but had no effect on Potato virus X and Cucumber mosaic virus infection. The full-length gene was cloned and revealed as an N. benthamiana nuclear-encoded chloroplast carbonic anhydrase (CA) and so designated NbCA. As compared with the accumulation of BaMV RNAs in NbCA-knockdown protoplasts, both plus- and minus-strand RNAs were reduced. We further fused NbCA with Orange fluorescent protein to confirm its localization in chloroplasts on confocal microscopy. However, transiently expressed NbCA in chloroplasts did not considerably increase BaMV accumulation. The addition of exogenous CA may not have any additive effect on BaMV accumulation because of the natural abundance of CA in chloroplasts. In an in vitro replication assay, the addition of E. coli-expressed NbCA enhanced exogenous template level (re-initiation and elongation) but not endogenous template level (only elongation). These results suggest that NbCA is possibly involved in re-initiation step of BaMV RNA replication. Further analysis indicated that proton concentration could influence the endogenous and exogenous template activities. Hence, our results implied that NbCA could be playing a role in harnessing proton concentration and favoring the replicase with the re-initiation template.